2011
DOI: 10.1136/ard.2010.148635
|View full text |Cite
|
Sign up to set email alerts
|

Synovial membrane immunohistology in early untreated juvenile idiopathic arthritis: differences between clinical subgroups

Abstract: There are significant differences in the histomorphometric features of synovial tissue between patient subgroups. Immunohistological examination of synovial membrane biopsies may provide further insight into early disease processes in JIA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…This was possibly due to the fact that we analyzed only JIA patients with oligoarticular involvement. As shown in a recent report, synovial CD20 expression differs significantly between polyarticular and oligoarticular JIA patient groups [31]. Patients with polyarticular involvement have three times higher expression of CD20 in the synovium.…”
Section: Discussionmentioning
confidence: 58%
“…This was possibly due to the fact that we analyzed only JIA patients with oligoarticular involvement. As shown in a recent report, synovial CD20 expression differs significantly between polyarticular and oligoarticular JIA patient groups [31]. Patients with polyarticular involvement have three times higher expression of CD20 in the synovium.…”
Section: Discussionmentioning
confidence: 58%
“…In early disease discrete protein isoforms may play a role in the different pathologies observed between oligoarticular and polyarticular synovium. In an earlier study we reported histological features which distinguish these JIA subgroups, including levels of vascularisation and white blood cell infiltration [16]. The likely pathological impact of synovial protein isoforms identified in the current study are subsequently discussed, along with their potential as therapeutic targets.…”
Section: Discussionmentioning
confidence: 71%
“…Primary antibodies used were monoclonal anti-integrin alpha 2b antibody (ITA2B) (Abcam, Cambridge, UK), monoclonal anti-peroxiredoxin 2 (PRDX2) (Sigma, Dorset, UK) and polyclonal anti-myosin regulatory light chain 2 (MYL2) (Sigma, Dorset, UK). Immunostaining was performed using a standard protocol and staining was visualized using the diaminobenzidine (DAB) method [16]. Sections were counterstained with haematoxylin.…”
Section: Methodsmentioning
confidence: 99%
“…Early inflammation of the synovial membrane is histologically characterised by synovial hypertrophy with cellular infiltrates, oedema, and increased vascularity [ 29 ]. These pathological features of temporomandibular joint arthritis are evident on MRI as joint effusion, synovial thickening, bone marrow oedema and increased joint enhancement [ 2 , 6 , 26 , 30 ].…”
Section: Manifestations Of Temporomandibular Joint Arthritis (Figs mentioning
confidence: 99%